Central banking and economic integration - Holtrop, Marius Wilhelm; Per Jacobsson Foundation (Stockholm : [Per Jacobsson Foundation], 1968)
The 1968 per Jacobsson Foundation lecture was given in Stockholm on Thursday, May 16, 1968, as part of the four-day program celebrating the 300th anniversary of the Sveriges Riksbank.
"The 1968 Per Jacobsson Foundation lecture was given in Stockholm on Thursday, May 16, 1968 ..."
Issued also in French and Spanish.
osc 21/8/17
Loans
Keywords: Banks and Banking, Central; International Economic Integration